2014
DOI: 10.1002/pchj.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walker gender and observer gender on biological motion walking direction discrimination

Abstract: The ability to recognize the movements of other biological entities, such as whether a person is walking toward you, is essential for survival and social interaction. Previous studies have shown that the visual system is particularly sensitive to approaching biological motion. In this study, we examined whether the gender of walkers and observers influenced the walking direction discrimination of approaching point-light walkers in fine granularity. The observers were presented a walker who walked in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Another interesting finding is that the reference repulsion bias was lower for male PLWs than female PLWs. On one hand, the results indicate that the directions in the range of [-90°, 90°] were more biased towards the facing-toward direction (0°) for male PLWs than female PLWs, which is consistent with previous studies that found male PLWs showed stronger facing-towards bias than female PLWs [18,35,52]. On the other hand, the finding indicates that the direction estimates of male PLWs are more accurate than those of female PLWs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Another interesting finding is that the reference repulsion bias was lower for male PLWs than female PLWs. On one hand, the results indicate that the directions in the range of [-90°, 90°] were more biased towards the facing-toward direction (0°) for male PLWs than female PLWs, which is consistent with previous studies that found male PLWs showed stronger facing-towards bias than female PLWs [18,35,52]. On the other hand, the finding indicates that the direction estimates of male PLWs are more accurate than those of female PLWs.…”
Section: Discussionsupporting
confidence: 89%
“…In other work, Yang et al (2014) found that the discrimination of the PLW motion direction (left vs. right) was more difficult when the PLW was depicted as male (right panel in Figure 4) than when it was depicted as female (left panel in Figure 4) [35]. Furthermore, male participants exhibited greater sensitivity than female participants when discriminating the female PLW's motion direction.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Schouten and colleagues () interpreted this finding such that “if the facing bias reflects an adaptation to the higher cost of misinterpreting an approaching person, misinterpreting the approach of a female figure might be less of a risk than misjudging the approach of a more dangerous male figure” (p. 1259). However, it has also been reported that male observers perform better at judging the walking directions (approaching/retreating) of female walkers, which may reflect evolutionary significance of the opposite gender appearance (Yang et al, ).…”
Section: Body Motion and Body Language Readingmentioning
confidence: 99%